2017
DOI: 10.1152/ajpheart.00124.2017
|View full text |Cite
|
Sign up to set email alerts
|

Experimental cardiac radiation exposure induces ventricular diastolic dysfunction with preserved ejection fraction

Abstract: Breast cancer radiotherapy increases the risk of heart failure with preserved ejection fraction (HFpEF). Cardiomyocytes are highly radioresistant, but radiation specifically affects coronary microvascular endothelial cells, with subsequent microvascular inflammation and rarefaction. The effects of radiation on left ventricular (LV) diastolic function are poorly characterized. We hypothesized that cardiac radiation exposure may result in diastolic dysfunction without reduced EF. Global cardiac expression of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 60 publications
4
28
0
Order By: Relevance
“…Deregulation of miR‐155 is associated with different kinds of cancer, inflammation, cardiovascular disease, and viral infections . These diseases are highly correlated with oxidative stress . DENV infection results in the intracellular accumulation of reactive oxygen species which induced damage that has been associated with increased disease severity in DENV‐infected patients .…”
Section: Discussionmentioning
confidence: 99%
“…Deregulation of miR‐155 is associated with different kinds of cancer, inflammation, cardiovascular disease, and viral infections . These diseases are highly correlated with oxidative stress . DENV infection results in the intracellular accumulation of reactive oxygen species which induced damage that has been associated with increased disease severity in DENV‐infected patients .…”
Section: Discussionmentioning
confidence: 99%
“…Premature coronary heart disease, electrical conduct defects or valve abnormalities are often associated with RIHD (46). In the early phase, RIHD often presents as heart failure with preserved ejection fraction (HFpEF), characterized by LVH and diastolic dysfunction (1, 7, 8). Radiotherapy significantly improves cancer patient survival; however, in the long-term, patients are at risk of RIHD and subsequent heart failure which becomes a major health issue affecting outcome, quality of life and health care costs (1).…”
Section: Introductionmentioning
confidence: 99%
“…They have been shown to be mediated by oxidative stress, the activation of pathologic NO-cGMP-PKG signaling, cytokine and growth factor cascades such as IL-4, IL-13, Rho/ROCK pathway and transforming growth factor beta (TGF-β) (1, 7, 9, 13, 14). Histopathological examination of cardiac lesions of RIHD shows hypertrophic cardiomyocytes, inflammatory cells, fibroblasts, and excessive deposition of collagens (1, 7, 14). Radiation-induced hypertrophy and fibrosis of the myocardium ultimately leads to a decrease in elasticity, ductility, and the development of diastolic heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…Randomized trials have reported that radiotherapy can substantially reduce cancer recurrence and moderately reduce cancer mortality; however, cardiac radiation exposure increases the risk of heart failure, thus limiting the use of radiotherapy (1,2). Cardiac radiation exposure in a rodent model resulted in cardiomyocyte hypertrophy, left ventricular diastolic dysfunction, oxidative stress and myocardial fibrosis (3). However, the mechanisms responsible for these effects of radiotherapy remain unclear.…”
Section: Introductionmentioning
confidence: 99%